PENGARUH SUHU DALAM PEMBUATAN KARBON AKTIF DARI KULIT SALAK (Salacca edulis) DENGAN IMPREGNASI ASAM FOSFAT (H3PO4) - Muhammad Turmuzi, Arion Syaputra (Universitas Sumatera Utara, 2015)
This study was aimed to determine the yield, iodine and characteristics of activated carbon pore surface area. Activated carbon is made by impregnation method with phosphoric acid (H3PO4). Snake fruit peel that has been mashed 1-2 mm soaked with phosphoric acid for (H3PO4) with concentration 10% for 3 hours. Filtered and dried for 24 hours at 60 °C. Snake fruit peel that has been impregnated pyrolysis at 400- 600 °C for 1 hours. Snake fruit peel that has been pyrolysis cooled in a desiccator for 30 minutes and washed until neutral pH. Then dried to a constant mass. The results showed that the best yield at a temperature of 400 °C 71.70%. The best surface area is 4078,694 m2/g. While iodine best is 494,91mg/g at a temperature 600 °C.